Pengelolaan Limbah Bambu Menjadi Kerajinan Celengan Guna Meningkatkan Kreatifitas Anak-anak Dan Menambah Nilai Jual Limbah Bambu - Resa Nurmala; Sri Yesi Mardiana; Risela Karismania (Celebes Abdimas: Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract. This training program is implemented aimed at improving the creativity of Mekarasih children and utilizing waste used bamboo into crafts as well as learning media into a piggy bank that has artistic value and value to also have selling value.This training was held in Mekarasih Village on August 29-30, 2020. In the implementation of the piggy bank making program was attended by 7 children of Mekarasih Village, 2 students, and accompanied by a Guiding Lecturer 1 person. The methods of implementation of this training program include (1) Socialization of material delivery to participants, (2) Implementation of the practice of making used bamboo waste into a piggy bank, (3) Evaluation of activities including evaluation of the manufacturing process, and results. The result of this community service in the form of crafts from used bamboo waste into a piggy bank that has artistic value and selling value as well as for children's learning media to motivate to get used to saving early in addition to increasing the selling value of bamboo waste.